Modelling the impact of climate change on avocados future irrigation requirements in South Africa - Mendori, Thomas (Cranfield University, 2021)
Climate change will affect worldwide weather and crop development. Agriculture is a major concern around Groot Letaba catchment (South Africa), and future irrigation supply for avocado crops is at risk but remains unclear. This research focused on the impact of climate change on future irrigation demand of avocados, with a case study in Limpopo province, South Africa. The objective was to compare water demand between the baseline data (1982-2010) and projections for 2050 and 2080 and determine the potential effect of climate change on avocados’ irrigation requirements in the future. First, a weather generator was used to create 1000 future daily time-series of rainfall and temperature, following nineteen different General Climate Models, for two emissions scenarios. The outputs were used in a soil-water balance model to simulate irrigation requirements of avocados according to the different scenarios and years studied. Models’ average irrigation demand was found to increase by at least 8.7% by 2050, and up to 17.4% by 2080, with a notable dispersion of values and few models predicting a decrease. The frequency of exceeding annual irrigation capacity could reach 45% with mitigation and 58% without mitigation by 2080. Farmers are expected to have more difficulties providing sufficient irrigation to avocados trees and facing possible multi-year droughts. Mitigation appeared as essential to ensure the sustainability of avocado business.
Keywords: Groot letaba; LARS WG; wasim; mitigation scenarios; climate model